A study of the phenomenon of shyness among the students of the College of Basic Education (Journal of the College of Basic Education, 2023)
Societies of all kinds and degrees of sophistication in civilization care about their youth because they are heldhopes for its continuity, development and progress, and this category is becoming more and more important in developing societies due to the need for thesecommunities to accelerate the process of national and comprehensive development, which is primarily responsible foron its youth, and this is what makes us see in the face of this generation the future of nations and civilizations and the future of manSame.(Al-Tai: 2001, pg. (5).The university stage is a stage for qualifying young people to take responsibility and have proper knowledge of the requirements ofThe age of science and technology, as it is a period of preparation and rehabilitation to think about solving the problems of society and payThere is no doubt that nations have given this category a great deal of attentionIn her academic family, her interest is also directed towards creating a strong personality that can think.scientifically sound.(Al-Tikriti: 1990, p. (115).The university is of great importance in building societies, as it is an institution for scientific research and it is a laboratory.To prepare vital information and ideas to serve the strategic goals of nation-building modern societiesUniversities are centers for research that transfers assets to a better state.(Al-Tai: 2001, pg. 15).Universities are racing to set the model for the integrated university personality that can controlEmotions satisfactory control and deal with others properly to achieve the goals of human society.(Al-Tikriti: 1990, pg. (115).The issue of linking higher education with the world of work raises a number of issues and problems thatIt requires an objective, scientific consideration, as the dichotomy and weakness between the two sides is noted.Clearly and tangibly, this division has created a double situation that makes the issue of harmonizing the education sector* Research problem: The requirements of the labor market are the main focus of the debate.(Bou Batania: 1990, p. 39Scientists and educators have been interested in studying human life, as it is at the forefront of issues with great values thatScientists in their various specializations have been preoccupied, and the issue of the individual's understanding of his abilities and capabilities has become an issue.A mission for him and the community and the ultimate goal of community development is the individual's progress and growth.(Saeed: 2001, pg. (1).The most powerful emotion affecting thinking, remembering, paying attention and other mental processes is fear.intense anger and related anxiety, shyness and confusion, and that shyness is one of the statesThe emotionality that accompanies fear when the individual fears the current situation surrounding him, and shyness may arise